Meet & Greet Raya 2025: colors of raya with international students - UiTM, UiTM Global (Office of International Affairs (OIA), 2025)
On 23 April 2025, UiTM Global proudly hosted the Meet and Greet Raya celebration, welcoming 70 international students from countries including China, Pakistan, Indonesia, Oman, Kazakhstan, Nigeria, Saudi Arabia, France, and Brunei. Held at the Foyer of Kompleks Antarabangsa, the event offered an immersive introduction to Hari Raya Aidilfitri in Malaysia